Case for diagnosis. Infraorbital schwannoma()() - Reyna-Rodríguez, Irving Llibrán (An Bras Dermatol, 2021)
We report a 40-year-old man, with an unremarkable personal and family history, who presented for evaluation of an asymptomatic papule located on his right cheek. Histopathology revealed an encapsulated neoplasm within the dermis; composed by narrow, elongated, and wavy cells with an ill-defined cytoplasm, dense chromatin and tapered ends interspersed with collagen fibers. Pathologic findings were consistent with tissue of Antoni B pattern. The diagnosis was an infraorbital schwannoma. The incidental finding of rare tumors like this, should make clinicians consider a greater spectrum of differential diagnoses for a unilateral skin-colored papule on the cheek of patients.